Minimum inhibitory concentration of the combination of quaternary ammonium compound with ethylenediaminetetra-acetic acid (EDTA) towards hand isolated Staphylococcus Epidermidis - Maria, Dyah Ika (Faculty of Dentistry Universitas Padjadjaran, Indonesia, 2009)
The aim of this study was to determine the Minimum Inhibitory Concentration (MIC) of the combination of Quaternary ammonium compound with Ethylenediaminetetra-acetic acid (EDTA) towards hand isolated Staphylococcus epidermidis for preventing the cross infection. The Minimum Inhibitory Concentration was determined based on a serial dilution method in 1/1000, 1/2000, 1/4000, 1/8000, 1/16000, 1/32000, 1/64000, 1/128000 concentration with two repetitions. The result showed that the 1/4000 concentration of the combination of Quaternary ammonium compound with Ethylenediaminetetra-acetic acid was the MIC. In conclusion, the combination of Quaternary ammonium compound with Ethylenediaminetetra-acetic acid had an antibacterial effect towards Staphylococcus epidermidis with the MIC in 1/4000 concentration.